Evaluating the Legitimacy of the Investor-State Dispute Settlement Mechanism for the AfCFTA (Strathmore Law Review, 2022)
Phase two of the negotiations on the African Continental Free Trade Area (AfCFTA) has begun. This phase includes negotiating the protocol on investment. The International Investment Regime (IIR) allows foreign investors to institute proceedings against states through Investor State Dispute Settlement (ISDS), which is criticised as undergoing a ‘legitimacy crisis’. This paper assesses the legitimacy of ISDS to evaluate whether it is a suitable mode of adjudicating international investment disputes in the AfCFTA. Accordingly, it sets out the criteria to be used in assessing legitimacy and further uses these criteria to appraise the legitimacy of ISDS, ultimately demonstrating that the present ISDS framework lacks sufficient legitimacy to be adopted as the mode of adjudicating international investment disputes in the AfCFTA. This is because of the perception that ISDS is unfair and biased due to its imperial and neo-colonial background and the excessive corporate power it grants to foreign investors. ISDS is also lacking in transparency and democratic values and conflicts with the AfCFTA’s objective of sustainable and inclusive socio-economic development. The paper advocates against the inclusion of ISDS in the AfCFTA protocol on investment and asserts that the challenge is in finding a mode of adjudication that is more equitable and inclusive than ISDS.